Chitinase Producing Bacterial Dynamics among Different Chitin Exposed Sampling Sites - Balaiya, Anandaraj; Thiagarajan, Mekala (Asian Journal of Biological and Life Sciences, 2025)
Background: Chitinase-producing bacteria help manage chitinous waste and act as biocontrol agents. Materials and Methods: Soil samples from seven chitin-exposed sites were screened; potent isolates evaluated for chitinolytic activity and temperature tolerance. Results: Several isolates (Citrobacter sp., Bacillus sp.) showed strong chitinase activity with optimal activity across temperature ranges. Conclusion: Chitin-exposed soils are promising sources of chitinase producers for biocontrol.
Keywords: Chitinase; Chitin; Enzyme